Shear Strength of One-Way Slabs Subjected to Concentrated Loads - Al-Bayati, Ahmed F.; Farhan, Omar S.; M. Taki, Zahir Noori (Civil Engineering Journal, 2025)
Reinforced concrete (RC) one-way slabs without transverse reinforcement are found extensively in bridge constructions. In the presence of concentrated loads (CLs) close to the supports, the shear strength (SS) of such slabs is usually determined using design expressions provided by the codes of practice that were derived originally from tests performed on beams or one-way slabs that were loaded along their entire width, which are inconsistent with the actual shear failure mechanism of one-way slabs under CLs. This paper presents an empirical SS model developed using the gene expression programming method (GEP), where the SS is related to six influencing parameters. The proposed model is derived employing the test results of 238 RC one-way slabs that experienced shear failure from the literature. The accuracy of the proposed model is measured using several statistical indices and compared with the existing shear design methods. The GEP model agreed favorably with the test results. The GEP model was also employed to conduct a parametric study for further validation and sensitivity analysis to define the contribution of input parameters to the SS. The parametric study demonstrated the efficiency of the GEP model in replicating the physical behavior, and the sensitivity analysis revealed that the SS is sensitive to the concrete strength and the shear span-effective depth ratio.